Convergence and Psychometric Properties of Character Strengths Measures: The VIA-IS and the VIA-IS-R. Issue 1 (2nd January 2023) - Vylobkova, Valentina; Heintz, Sonja; Gander, Fabian; Wagner, Lisa; Ruch, Willibald
Abstract: This study compares the German versions of the original measure of character strengths (VIA-IS) with its latest revision (VIA-IS-R) regarding reliability and convergent, discriminant, and criterion-related validity. A sample of 499 German-speaking adults (79% women, mean age: 33.3 years) provided self-reports of character strengths (VIA-IS, VIA-IS-R) and several criteria: Core virtues, thriving, and moral behaviors. Results suggested that both measures showed satisfactory internal consistency and converged well in a multitrait-multimethod analysis. Further, both measures were comparable regarding their relationships with the criteria. Overall, the results of the current study suggest that both questionnaires are reliable and valid, and that findings based on these instruments can be considered highly comparable.